Pelaksanaan Asuhan Kebidanan Ibu Hamil, Nifas, Balita pada Pengabdian Masyarakat Desa Mojokerto - Margita Widi Esti; Vistra Veftisia; Syahrianti; Wahyu Hastuti Utami (Universitas Ngudi Waluyo, 2022)
Public health problems are problems that arise in the community and affect the degree of public health. So as a form of community service students are obliged to analyze, formulate problems, determine problem priorities, diagnose problems, plan activities, and implement them so that evaluation of all series of activities can be carried out with the aim of increasing health status through community service activities, especially in Mojokerto Village. Kedawung District, Sragen Regency. Based on the results of an assessment conducted for 7 days, starting from October 30 to November 6, 2022, several problems have been found including problems in pregnant women, postpartum women and toddlers, these problems include a lack of mother's knowledge of danger signs of pregnancy Lack of mother's knowledge regarding high-risk pregnancies and high-risk pregnancies where there is a lack of mother's knowledge about the importance of Fe tablets, Lack of knowledge of postpartum mothers about the importance of using contraception, Lack of mother's knowledge about improving the quality of breast milk, Lack of knowledge of mothers about exclusive breastfeeding, Lack of knowledge of mothers about giving MP-ASI . The purpose of this activity is to increase mother's knowledge, and after carrying out activities including counseling and disclosure there is an increase in mother's knowledge. In pregnant women, the post-test results found that there was no lowest score and the average and highest score was 10. These results show that the provision of information is very useful for increasing the knowledge of pregnant women. In postpartum mothers after being given an IEC about the importance of contraceptive use and contraceptive choices, mothers come to understand and understand the importance of contraceptive use, and postpartum mothers plan to choose birth control according to their needs as a contraceptive option to be used. After a demonstration of acupressure to improve the quality of breast milk, mothers understand and understand how to improve the quality of breast milk and mothers are willing to do independent acupressure therapy at home. In baduta mothers, the post test results obtained 3 baduta mothers answered 9 correct answers and 10 baduta mothers answered 10 correct answers with a total score of 10. Here there is an increase in knowledge between before and after the IEC is carried out regarding the importance of exclusive breastfeeding and the provision of complementary milk. Abstrak Masalah kesehatan masyarakat merupakan masalah yang timbul di tengah masyarakat dan mempengaruhi derajat kesehatan masyarakat. Maka sebagai bentuk pengabdian masyarakat mahasiswa berkewajiban untuk menganalisa, merumuskan masalah, menentukan prioritas masalah, menegakkan diagnosa masalah, melakukan perencanaan kegiatan, serta mengimplementasikannya sehingga dapat dilakukan evaluasi atas semua rangkaian kegiatan dengan tujuan untuk meningkatkan derajat kesehatan melalui kegiatan pengabdian masyarakat khususnya di Desa Mojokerto, Kecamatan Kedawung, Kabupaten Sragen. Berdasarkan hasil pengkajian yang dilakukan selama 7 hari yaitu dimulai dari tanggal 30 Oktober hingga 06 November 2022, telah ditemukan adanya beberapa masalah diantaranya adalah terdapat permasalahan pada ibu hamil, ibu nifas dan balita, permasalahan tersebut meliputi kurangnya pengetahuan ibu terhadap tanda bahaya kehamilan Kurangnya pengetahuan ibu mengenai resiko tinggi kehamilan dan kehamilan beresiko dimana kurangnya pengetahuan ibu mengenai pentingnya tablet Fe, Kurangnya pengetahuan ibu nifas tentang pentingnya penggunaan alat kontrasepsi, Kurangnya pengetahuan ibu tentang meningkatkan kualitas ASI, Kurangnya pengetahuan ibu tentang ASI eksklusif dimana, Kurangnya pengetahuan ibu tentang pemberian MP-ASI. Tujuan dari kegiatan ini dalah untuk meningkatkan pengetahuan ibu, dan setelah dilakukan pelaksanaan kegiatan meliputi penyuluhan dan demonstrasi terdapat peningkatkan pengetahuan ibu. Pada ibu hamil hasil post test didapatkan bahwa tidak terdapat nilai terendah dan nilai rata-rata dan tertingginya adalah 10. Hasil ini menunjukkan bahwa pemberian informasi sangat bermanfaat untuk meningkatkan pengetahuan ibu hamil. Pada ibu nifas setelah diberikan KIE tentang pentingnya penggunaan kontrasepsi dan pilihan kontrasepsi, ibu menjadi mengerti serta memahami tentang pentingnya penggunaan kontrasepsi, dan Ibu nifas berencana memilih KB sesuai kebutuhannya sebagai pilihan kontrasepsi yang akan di gunakan. Setelah dilakukan demonstrasi akupresur untuk meningkatkan kualitas ASI, ibu mengerti dan memahami cara meningkatkan kualitas ASI dan Ibu bersedia melakukan terapi akupressure mandiri di rumah. Pada ibu baduta hasil post test didapatkan 3 ibu baduta menjawab 9 jawaban benar dan 10 ibu baduta menjawab 10 jawaban benar total nilai 10. Disini terjadi peningkatan pengetahuan antara sebelum dan setelah dilakukan KIE mengenai pentingnya ASI eksklusif dan pemberian MP ASI.